2021
DOI: 10.3389/fimmu.2020.602605
|View full text |Cite
|
Sign up to set email alerts
|

CD39+ Regulatory T Cells Attenuate Lipopolysaccharide-Induced Acute Lung Injury via Autophagy and the ERK/FOS Pathway

Abstract: Acute respiratory distress syndrome (ARDS) is characterized by an uncontrollable cytokine storm, which is associated with high mortality due to lack of effective treatment. Regulatory T cells (Tregs) play an indispensable role in maintaining immune homeostasis and CD39 is considered as a functional cell marker of Tregs. In this study, we aimed to evaluate the effect of CD39+ Tregs on acute lung injury (ALI) and investigate the frequency of CD39+ Tregs in ARDS patients. We found that after lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…As reported, Treg exerts a critical role in sustaining immune homeostasis, and CD39, an exonucleotide enzyme of hydrolytic proinflammatory ATP, is considered as a functional cell marker of Treg [20]. Antecedent studies have illuminated Tregs implicates in the pathogenesis of sepsis via stimulating immunosuppression [21].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, Treg exerts a critical role in sustaining immune homeostasis, and CD39, an exonucleotide enzyme of hydrolytic proinflammatory ATP, is considered as a functional cell marker of Treg [20]. Antecedent studies have illuminated Tregs implicates in the pathogenesis of sepsis via stimulating immunosuppression [21].…”
Section: Discussionmentioning
confidence: 99%
“… 25 Another study reported that CD39+ regulatory T cells attenuate LPS-induced ALI via autophagy and ERK/FOS pathway. 26 However, bioinformatics analysis of ARGs has not been well explored in sepsis-induced ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest elevated autophagy is a maladaptive response caused by incomplete autophagy activation, and therefore, completing or enhancing autophagy will alleviate ALI and improve the prognosis (Lo et al, 2013;Lin et al, 2014;Zhao et al, 2019;Nosaka et al, 2020;Peng et al, 2021;Zhang et al, 2021). On the contrary, other studies indicate activated autophagy is a pathogenic factor leading to ALI, and thus, inhibiting autophagy benefits the treatment (Sun et al, 2012;Hu et al, 2014;Zhu et al, 2017;Slavin et al, 2018;Chen et al, 2020;Li et al, 2020). In this study, we detected activated autophagy in CLPinduced ALI damages, as represented by the increased number of autophagosomes under TEM, the up-regulated expression and co-localization of LC3II and Beclin1, and the down-regulation of p62.…”
Section: Discussionmentioning
confidence: 99%